Endoscopic transpapillary gallbladder stenting using a newly designed plastic stent for acute cholecystitis - Nakahara, Kazunari; Michikawa, Yosuke; Morita, Ryo; Suetani, Keigo; Morita, Nozomi; Sato, Junya; Tsuji, Kensuke; Ikeda, Hiroki; Matsunaga, Kotaro; Watanabe, Tsunamasa; Matsumoto, Nobuyuki; Kobayashi, Shinjiro; Otsubo, Takehito; Itoh, Fumio (Endoscopy International Open, 2019)
Background and study aims Biliary plastic stents are generally substituted for gallbladder stents in endoscopic transpapillary gallbladder stenting (EGBS), there is no sufficient evidence about what type of plastic stent is suitable. We examined outcomes of EGBS using standard biliary stents and a novel stent for acute cholecystitis and evaluated the efficacy of the novel stent.Patients and methods Seventy patients with acute cholecystitis in whom EGBS was performed were evaluated retrospectively. We performed EGBS in 23 patients using the novel stent (novel stent group) and 47 patients using standard biliary stents (pigtail: 35, straight: 12) (control group). In the two groups, we examined outcomes of EGBS.Results There were no significant differences in patient backgrounds or rates of technical success, clinical success, or early adverse events (AE) between the novel stent group and the control groups. However, rates of late AEs were 4.3 % in the novel stent group (liver abscess: 1) and 40.4 % in the control group (stent migration: 15, recurrence of cholecystitis: 4), indicating a significantly higher rate in the control group (P = 0.004). The rate of stent migration was significantly higher in the control group (P = 0.006). Multivariate analysis identified a straight type stent as the risk factor for stent migration (odds ratio: 8.81, 95 % confidence interval: 1.66 – 46.83).Conclusions The novel stent had significantly lower rates of late AEs and stent migration. Thus, for long-term stent placement, the novel stent was more effective than traditional biliary stents.